AKT/GSK-3β regulates stability and transcription of snail which is crucial for bFGF-induced epithelial–mesenchymal transition of prostate cancer cells - Liu, Zong-cai; Wang, Hong-sheng; Zhang, Ge; Liu, Hao; Chen, Xiao-hui; Zhang, Fan; Chen, Dan-yang; Cai, Shao-hui; Du, Jun (Biochimica et biophysica acta, 2014)
Epithelial–mesenchymal transition (EMT) plays a pivotal role in the development of metastatic cancers. Basic fibroblast growth factor (bFGF) is significantly elevated in metastatic prostate cancers, which has been mentioned mainly to induce EMT in normal cells. However, there is no description about bFGF induced EMT and its underlying mechanism in prostate cancer cells. Western blotting, immunofluorescence and qRT-PCR assays were used to study protein or mRNA expression profiles of the EMT. Wound healing scratch, migration and invasion assays were used to test the motility of cells undergoing EMT. More methods were used to explore the underlying mechanisms. We demonstrated that bFGF promoted EMT and motility of human prostate cancer PC-3 cells. Both protein and mRNA expression of Snail were rapidly increased after bFGF treatment. Ectopic expression of Snail triggered EMT and enhanced cell motility in PC-3 cells, and knockdown of Snail almost abolished bFGF induced EMT, suggesting the critical role of Snail. Mechanistic study demonstrated that bFGF promoted the stability, nuclear localization and transcription of Snail by inhibiting the activity of glycogen synthase kinase 3 beta (GSK-3β) through phosphatidylinositide 3 kinases (PI3K)/protein kinase B (AKT) signaling pathway. It is concluded that bFGF can promote EMT and motility of PC-3 cells, and AKT/GSK-3β signaling pathway controls the stability, localization and transcription of Snail which is crucial for this bFGF induced EMT. To our knowledge, this is the first study to demonstrate that bFGF can induce EMT via AKT/GSK-3β/Snail signaling pathway in prostate cancer cells. •bFGF can promote EMT and motility of human prostate cancer PC-3 cells.•bFGF increases both the protein and mRNA expression of Snail.•Snail is crucial for bFGF induced EMT in PC-3 cells.•bFGF regulates the stability, localization and transcription of Snail.•bFGF also regulates the transcription of Snail.